Deiksis dalam Kumpulan Cerita Pendek Yang Aku Pikirkan Karya Wagiman dan Khaidar Naufal Pasingsingan - Rahel Julia Andina; Misnawati Misnawati; Indra Perdana; Linggua Sanjaya Usop; Isti Rahayu (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2025)
This study aims to (1) describe the types of deixis contained in a collection of short stories titled Yang Aku Pikirkan by Wagiman and Khaidar Naufal Pasingsingan, (2) describe the function of deixis contained in a collection of short stories titled Yang Aku Pikirkan by Wagiman and Khaidar Naufal Pasingsingan, (3) describe the implications of this research on learning to write short stories in high school. This study uses a descriptive qualitative approach. The source of data in this study is the text of the short story collection Yang Aku Pikirkan by Wagiman and Khaidar Naufal Pasingsingan. The data research procedure in this study is carried out by reading, marking, sorting, identifying, and analyzing data. The results of this study show that there are five types of deixis in the collection of short stories, namely the personal deixis, the deixis of time, the deixis of place, the deixis of discourse, and the social deixis. There are 5 short stories that have all kinds of deixis in full in it, namely, Sebuah Pelajaran, Novel Tidak Bermutu, Idul Adha bersama Teman, Sore Hari di Pantai Kuta, and Bangkit. The most data is found in the personal deixis and deixis of discourse. The use of deixis in short story collections has implications for learning to write short stories in high school, KD 4.9 constructs a short story by paying attention to the elements that build short stories. Students can learn the importance of deixis in short stories as an addition to students' advanced knowledge in making short stories after paying attention to the elements of short story builders, so as to produce short stories that can be enjoyed when reading it.